2021
DOI: 10.1097/pcc.0000000000002664
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four–Hour Esophageal pH Measurement in Mechanically Ventilated Children: A Prospective Cohort Study*

Abstract: Objectives: To assess the prevalence of gastroesophageal reflux in mechanically ventilated children using 24-hour esophageal pH-metry and its role as a risk factor for ventilator-associated pneumonia. Design: Prospective cohort study. Setting: PICU of a tertiary care hospital from North India. Patients: Mechanically ventilated children 1–15 years old in PICU from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Not only that, the only VAP suspicion should be managed by the use of essential antibiotics 14 . This demonstrates the importance of meeting the clinical criteria in preventing inappropriate antibiotic therapy in the diagnosis of VAP 15 .…”
Section: Discussionmentioning
confidence: 86%
“…Not only that, the only VAP suspicion should be managed by the use of essential antibiotics 14 . This demonstrates the importance of meeting the clinical criteria in preventing inappropriate antibiotic therapy in the diagnosis of VAP 15 .…”
Section: Discussionmentioning
confidence: 86%
“…A single-center prospective cohort study evaluated the prevalence of gastroesophageal reflux (GER) in mechanically ventilated children using 24-h esophageal pH monitoring and the incidence of ventilator-associated pneumonia (VAP). They found that children with acidic GER had a decreased frequency of VAP though this was not statistically significant [64]. Studies to date suggest potential harm in prescribing these medications, while not showing a clear benefit in outcomes.…”
Section: Enteral Nutritionmentioning
confidence: 96%